PENGGUNAAN COMMUNICATION GAMES PADA PELATIHAN BAHASA INGGRIS BAGI SISWA-SISWA SMPN 4 NUSA PENIDA DESA LEMBONGAN - N.M.A. Widiastuti; I G.A.G. Sosiowati; S.A.I. Maharani; N.K.S. Rahayuni (Buletin Udayana Mengabdi, 2017)
The aims of the English training with communication games to the students at SMPN 4 Nusa Penida, Desa Lembongan are to find out the English vocabulary of the students before the training was given and to describe the students’ communication development in English after the training was given. The six-sessions English training was given to the students in class VII (130 students) and class VIII (129 students). The TPR (Total Physical Response) was used during the training. The training materials were taken from the books “Beginners Communication Games” (2007) and “Elementary Communication Games” (2008) by Jill Hadfield with the six topics chosen based on their needs: 1) Lost in the post, 2) Crossroad, 3) Visiting Friends, 4) World map, 5) Room service, dan 6) The restaurant game. The results show that before the training was given, on average the students in class VII were able to write 3-8 words/sentences, menwhile the students in class VIII were able to write 5-12 words/sentences in 10 minutes. The students’ communication in English after the training was well developed, that is on the first day of the training they were still difficult to communicate in English, however, on the second day, they were able to greet the instructors in English, active in the classroom activity and learn English through communication games actively and without shame. Their English vocabulary is also developed after the training.